Quality of Life in Osteoporosis: A Controlled Study - Halim Yılmaz; Gülten Erkin; Halime Almula Demir Polat; Sami Küçükşen; Ali Sallı; Hatice Uğurlu (Galenos Yayinevi, 2012)
Aim: To evaluate quality of life in women without vertebral and nonvertebral fractures, with postmenopausal osteoporosis (PMO), osteopenic and normal bone mineral density (BMD), and to determine effective factors on quality of life. Materials and Methods: Without fractures, 266 women with PMO, 310 with osteopenia and 255 with normal women BMD were enrolled in the study. BMD measurement was performed on lumbar vertebra (L1-L4) and femur neck via dual energy X-ray absorbtiometry (DXA). Quality of life was assessed with Quality of Life Questionnaire of the European Foundation for Osteoporosis (QUALEFFO). QUALEFFO total scores and subscales were compared in all groups. Factors about quality of life in women with PMO were defined with correlation analysis. Variations of the highest correlation and quality of life were included into linear regression model. Results: In non-fractured women with PMO, QUALEFFO total scores and subscales were higher than those with osteopenia and normal BMD. In women with PMO, a positive correlation was found between QUALEFFO total scores, and age, Body Mass İndex (BMI), parity and duration of menopause, and a negative correlation between QUALEFFO total scores, and level of education, economical status and femur neck BMD scores. In linear regression analysis, among significant factors of quality of life were BMI, femur neck BMD, parity and duration of menopause. Conclusion: Our results indicate that quality of life in non-fractured women with PMO is disordered higher than those with osteopenia and normal BMD, and quality of life are affected by numerous factors. (Turkish Journal of Osteoporosis 2012;18: 47-52)